Thermal Modelling of Cell-to-Cell Fire Propagation and Cascading Thermal Runaway Failure Effects for Lithium-Ion Battery Cells and Modules Using Fire Walls. Issue 14 (22nd October 2016) - Larsson, Fredrik; Anderson, Johan; Andersson, Petra; Mellander, Bengt-Erik
Abstract : A model is presented for predicting the cell-to-cell propagation of a thermal runaway/fire in a lithium-ion battery cell to neighboring cells by simulating the temperature development in neighboring cells. The modelling work comprises of two major steps; setting up a model of the cells including the thermal properties of the cells, and then validating the model through experiments where the boundary conditions in the validation test must be determined carefully. The model is developed to allow a fast evaluation of several different preventive means of thermal insulation, it is not modelling the pack and cells to a great detail. Still the experimental validation indicates that the model is good enough to fulfil its purpose of the model. A feasibility study using the model is conducted assessing two different types of fire walls between battery modules of 10 cells. The results show that there is a substantial risk for a cascading of thermal events in a battery pack, although cooling systems and fire walls may mitigate these risks.